Values of the Code of Ethics of Dental Services Qur'anic Perspective: Analytical Study of the Interpretation of Related Verses KODEKGI - Wulansari, Retno; Huda, Ade Naelul; Ulhaq, Ziyad (CV. Publikasi Indonesia, 2024)
This research aims to analyze KODEKGI values from the perspective of Qur'anic interpretation, as well as to analyze the implementation of KODEKGI service values from a Qur'anic perspective on Muslim dentists. This research uses a qualitative method by combining two research locations, library research and field research. Primary data were generated from field research through direct interviews with dentist respondents through sampling methods, as well as a literature study of three tafsir books in the style of al-'adabi al-ijma'i and Tafsir Tahlili of the Ministry of Religion of the Republic of Indonesia. While the secondary data is generated from the research library. The data analysis technique that the author used in this research is the content analysis technique. The two formulations produced by this study are: first, ten articles related to services to patients in KODEKGI have values that are in line with the Qur'an. Secondly, a review of Muslim doctors' services against KODEKGI shows their original intention was to abide by the existing rules. There are Qur'anic values in KODEKGI triggering Muslim dentist respondents to run KODEKGI to worship Allah.